1994
DOI: 10.1161/01.atv.14.3.434
|View full text |Cite
|
Sign up to set email alerts
|

High fibrinogen and plasminogen activator inhibitor activity in growth hormone-deficient adults.

Abstract: Hypopituitary patients on routine replacement therapy except growth hormone (GH) have an increased risk of death from cardiovascular diseases compared with healthy subjects. Untreated GH deficiency might explain the premature death from vascular disease. Plasminogen activator inhibitor (PAI-1) activity, fibrinogen, insulin, blood lipid, and blood pressure levels were studied in 20 GH-deficient adults (10 men, 10 women) 50±ll years old with routine hormone replacement therapy (except GH) and compared with 20 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
0
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 20 publications
3
93
0
8
Order By: Relevance
“…Sartorio et al reported increased plasma levels of PAI-1, fibrinogen, and thrombin-antithrombin complex in 24 patients with adult-onset GH deficiency (85). Similarly, Johansson et al showed a significant increase in plasma fibrinogen and PAI-1 activity levels in 20 GH-deficient adults, and demonstrated reversal of these hemostatic abnormalities after 2 years of recombinant human GH replacement therapy (92,93). Almost identical results were observed in a small intervention study by Kvasnicka et al (94), who confirmed a favorable effect of a 1-year GH replacement therapy on plasma fibrinogen, PAI-1, intercellular adhesion molecule-1, and E-selectin levels in GH-deficient adults (95).…”
Section: Gh Deficiencymentioning
confidence: 96%
“…Sartorio et al reported increased plasma levels of PAI-1, fibrinogen, and thrombin-antithrombin complex in 24 patients with adult-onset GH deficiency (85). Similarly, Johansson et al showed a significant increase in plasma fibrinogen and PAI-1 activity levels in 20 GH-deficient adults, and demonstrated reversal of these hemostatic abnormalities after 2 years of recombinant human GH replacement therapy (92,93). Almost identical results were observed in a small intervention study by Kvasnicka et al (94), who confirmed a favorable effect of a 1-year GH replacement therapy on plasma fibrinogen, PAI-1, intercellular adhesion molecule-1, and E-selectin levels in GH-deficient adults (95).…”
Section: Gh Deficiencymentioning
confidence: 96%
“…During the past two decades, evidence has emerged linking hypopituitarism with cardiovascular risk factors, including hyperlipidaemia (11,12,13,14), visceral adiposity (15,16), insulin resistance (17) and vascular endothelial dysfunction (18,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Much is made of the increased cardiovascular mortality in hypopituitary GH-deficient patients reported in two well-conducted epidemiological studies from Sweden (7,8). This, coupled with the finding of premature atherosclerosis (9), unfavourable lipid (10) and cardiovascular risk profile (11) together with favourable changes on GH replacement (5, 6, 11), has prompted some to suggest that GH replacement may lead to a lessening of the cardiovascular mortality in this patient group. However, there are concerns that GH replacement involves administration of an anabolic and potentially mitogenic substance to a patient group that contains many with previous or residual pituitary tumours.…”
Section: Introductionmentioning
confidence: 99%